The Integration of Hanafi Mazhab Qawā'id Fiqhiyyah into Indonesia's Halal Certification System - Fithri Dzikrayah; Hasan Bisri; Ayi Yunus Rusyana; Hasna Safira (Al-Mustashfa: Jurnal Penelitian Hukum Ekonomi Syariah, 2026)
Indonesia’s halal certification system possesses a strong positive legal foundation, but its normative relationship with Hanafi legal principles and its implications for business governance require further clarification. This study aims to analyse Hanafi legal principles as a normative framework for evidentiary verification, legal certainty, prevention of harm, and responsible business governance in Indonesia’s halal certification system. It employs normative legal research using statutory and conceptual approaches. Primary legal materials include Law Number 33 of 2014, Law Number 6 of 2023, and Government Regulation Number 42 of 2024, while secondary materials comprise classical and contemporary Hanafi jurisprudence, literature on qawāʿid fiqhiyyah, and studies on halal certification and corporate compliance. The findings demonstrate three principal functions. First, the evidentiary principle of al-ithbāt, supported by al-aṣl baqāʾ mā kāna ʿalā mā kāna, legitimises the verification of ingredients, suppliers, production processes, and contamination risks while maintaining certified status until valid evidence proves a relevant change. Second, al-yaqīn lā yazūlu bi al-shakk protects legal certainty from unsupported doubt. Third, darʾ al-mafāsid muqaddam ʿalā jalb al-maṣāliḥ positions certification as a preventive mechanism against Sharia violations and legal uncertainty. The study concludes that halal certification represents a functional normative correspondence with Hanafi jurisprudence and operates as a modern Islamic legal and business-governance instrument supporting compliance, risk mitigation, market trust, and sustainable business practices.